The unstable shoulder in the adolescent athlete - Walton, J.; Paxinos, A.; Tzannes, A.; Callanan, M.; Hayes, K.; Murrell, G. A. (The American Journal of Sports Medicine, 2002)
Shoulder dislocation and subluxation occur frequently in athletes, with peaks in the second and sixth decades. The majority of traumatic dislocations are in the anterior direction. The most frequent complication of shoulder dislocation is recurrence-a complication that occurs much more often in the adolescent population. The dynamic (muscular) and static (predominantly capsuloligamentous and labral) restraints to shoulder instability are now well defined. Recent surgical procedures for shoulder instability have become less interventional and have focused on restoring disrupted static restraints. The aim of rehabilitation is to enhance the dynamic muscular and proprioceptive restraints to shoulder instability.